Quality of life of the elderly: a comparison between community-dwelling elderly and in social welfare institutions - Kiik, Stefanus Mendes; Nuwa, Muhammad Saleh (MEDISAINS, 2020)
Background: Quality of life (QoL) among the elderly is a neglected issue, especially in developing countries, including Indonesia. The QoL of the elderly is dependent on four domains. Living arrangements play an important role in determining QoL.Objective: The present study aimed to compare the differences in QoL among community-dwelling elderly and in social welfare institutions.Methods: This was a cross-sectional study. Participants were sampled from two settings: social welfare institutions and the community. The study subjects in each area were selected using a simple random technique. The total sample were 163 respondents. QoL was assessed through the WHOQOL-Bref. Data analysis was performed by the Mann-Whitney U Test.Results: There were significant differences depending on the residence of the elderly: the average QoL in a community is higher (84.16) than in social welfare institutions (63.95), and p-value < 0.001.Conclusions: The results of our study indicate that community-dwelling elderly have higher QoL compared to residents of social welfare institutions.